The Widening Space of Postsecondary Education - Van Damme, Dirk (International Higher Education, 2023)
Massification of postsecondary education participation has been predominantly met by expanding higher education institutions. But the risk of over-schooling and the demand for increasingly diversified skills now require postsecondary education systems to expand vocational and subdegree programs. At the same time, bridging the divide between the higher and further education subsectors will lead to a more integrated but diversified postsecondary landscape.